Effectiveness of an Educational Program on Nurses’ Knowledge Concerning the Infection Control Guideline in Baghdad Teaching Hospital - jissir, saad; hassan, Huda (Iraqi National Journal of Nursing Specialties, 2017)
Objectives: the study aims to findout the effectiveness of educational program concerning infection control guideline on nurses, and to find out the relationship between effectiveness of program and types of hospital unit, age, level of education, and years of experience of nurses. Methodology: A quasi-experimental design study was carried out in Baghdad teaching hospital in the wards, for the period of December, 20th 2013 to September, 30th of July 2014, The study samples is composed of (60) nurses who have been actually working in the medical ward, blood disease, psychiatric ward, and neurological wards in Baghdad Teaching Hospital, those nurses are divided equally into the study and the control groups. The researcher constructed the educational program and instruments in order to reach the aims of this study, the program deals with (10) main domains related to infection control, and each domains consist of many items to assess the nurses knowledge, and the questionnaires consist of two parts; first is concerned with the demographic data for nurses; and the second part is concerned with the assessment of the nurses' knowledge about infection control methods. The data have been analyzed through the application of: descriptive frequency, percentages; mean of scores; and the inferential analysis that include: Analysis of variance, and the researcher used the SPSS version 20 to analysis of data. . Results: Most of the nurses 63.3% was females at age (20-29), in relation to marital status most of the samples was married, and graduated from nursing institute as educational level, (53.3%) of nurses have (1-9) years of experience and majority of nurses included with training course in Iraq but not related to infection control program , and the findings of present study revealed that there were statistical differences about the infection control knowledge of nurses between pre and post program and between the post study and post control group also there are statistical differences between level of education of nurses and infection control knowledge at P ≥0.05. Recommendation: The study recommends to application the world health organization (WHO) program of infection control program at all health centers and continuous medical educational program for all staff in the health center, and continuous follow up to applying the program to prevent spread of infection